Stambeni problemi, produženi život s roditeljima i odgoda ulaska u brak u Hrvatskoj - Akrap, Anđelko (Array, 2008)
In this paper, we investigate the relationship between housing problems, prolonged living with parents and marriage postponement in Croatia. We have used the data from two recent surveys to analyse this relationship. The fi rst survey involved childless singles in the age 35 to 44, and the second one working women in the age 20 to 40. The results indicate that costly housing, and more generally housing problems, have a signifi cant infl uence on a decision to enter into a marriage and the fertility motivation